Pathobiology of traumatic spinal cord injury: an overview - William A. Florez-Perdomo; Andrés Cardona-Cruz Guillermo; Ezequiel García-Ballestas; Abigail Castilla-Martínez; Yancarlos Ramos-Villegas; Loraine Quintana-Pájaro; Tariq Janjua; Amit Agrawal; Luis Rafael Moscote-Salazar (Egyptian Journal of Neurosurgery, 2024)
Abstract Traumatic spinal cord injury (SCI) or traumatic myelopathy is a devastating neurological condition and a heavy burden on the health system. There are inflammatory and structural biomarkers with well-defined profiles, and useful for determining the management and prognosis of this pathology. Laboratory studies have shown some utility in confirming the existence of a spinal cord injury. Little knowledge about the molecular processes that occur after a SCI is evident, and it is well known that its understanding is dispensable to establish therapeutic targets that improve the outcomes for this type of patient. Many studies have explored the role of structural and inflammatory markers and some structural and inflammatory biomarkers. In the present article, we review the ongoing research in the field of spinal injury and possible role of biomarkers in the management of these patients.